2015
DOI: 10.1016/j.jclepro.2015.04.073
|View full text |Cite
|
Sign up to set email alerts
|

International study on energy end-use data among industrial SMEs (small and medium-sized enterprises) and energy end-use efficiency improvement opportunities

Abstract: The industrial sector is important to study in terms of improved energy efficiency, being one of the major energy-using sectors and responsible for a major share of CO2 emissions.The energy end-use (EEU) in the industrial sector is complex in general as processes are intertwined and interrelated. Moreover, bottom-up data of EEU on an aggregated level is scarce.Data for total energy supply like electricity, oil, coal, and natural gas exists but bottom-up data of what processes these energy carriers are used in,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 20 publications
3
39
0
Order By: Relevance
“…The evaluation of the Swedish regional and German national energy audit programs has shown that the majority of the EEMs were proposed for generic (support) processes related to space heating, ventilation, compressed air systems, etc. For SMEs, support processes present larger aggregated energy use than production processes (Thollander et al, 2015a).…”
Section: Industrial Energy Audit Programs For Smesmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation of the Swedish regional and German national energy audit programs has shown that the majority of the EEMs were proposed for generic (support) processes related to space heating, ventilation, compressed air systems, etc. For SMEs, support processes present larger aggregated energy use than production processes (Thollander et al, 2015a).…”
Section: Industrial Energy Audit Programs For Smesmentioning
confidence: 99%
“…Another essential issue highlighted in the review is insufficiency of standardized approaches for industrial energy policy evaluation, which can play a crucial role for the perceived success of industrial policies (Harris et al, 2000). Also, homogeneous categorization of energy data for evaluation of industrial EEU policies is a further important aspect which would enable comparison of energy policies among different countries (Thollander et al, 2015a).…”
Section: Industrial Energy Audit Programs For Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…Price (2005), who reviewed 23 industrial voluntary agreement programs from 18 countries, and Rezessy and Bertoldi (2011), who reviewed EU voluntary agreement programs from 11 countries, these studies do not present in-depth findings on the implementation from various process categories. Moreover, if data did exist, comparisons would have been challenging as no uniform way of categorizing energy end-use measures resulting from industrial energy programs exists (Thollander et al, 2015).…”
Section: -38%mentioning
confidence: 99%
“…Another work [15] shows a study based on data collected in eight industrial buildings of automobile manufacturers in Italy and the assembly of a model to evaluate the impact of different actions which aimed at reducing energy consumption. On a different path, the work led by Thollander [16] dustry has the seventh largest potential, in absolute terms, for the conservation of thermal energy and total energy consumption and the third largest potential, in absolute terms, for the conservation of electricity [17]. The food and beverage sector inserted in the dairy industry has great potential for energy savings in various uses.…”
Section: Introductionmentioning
confidence: 99%